NOBLE GASES AND VOLATILE RECYCLING AT SUBDUCTION ZONES - Hilton D.R.; Fischer T.P.; Marry B. (My University, 2002)
Volatiles are lost from the Earth’s mantle to the atmosphere, hydrosphere and crust through a combination of subaerial and submarine volcanic and magmatic activity. These volatiles can be primordial in origin, trapped in the mantle since planetary accretion, produced in situ, or they may be recycled—re-injected into the mantle via material originally at the surface through the subduction process. Quantifying the absolute and relative contributions of these various volatile sources bears fundamental information on a number of issues in the Earth Sciences ranging from the evolution of the atmosphere and hydrosphere to the nature and scale of chemical heterogeneity in the Earth’s mantle. Noble gases have a pivotal role to play in addressing the volatile mass balance between the Earth’s interior and exterior reservoirs. The primordial isotope 3He provides an unambiguous measure of the juvenile volatile flux from the mantle (Craig et al. 1975). As such, it provides a means to calibrate other volatiles of geological and geochemical interest. A prime example is the CO2 flux at mid-ocean ridges (MOR): by combining estimates of the 3He flux at MOR with measurements of the CO2/3He ratio in oceanic basalts, Marty and Jambon (1987) derived an estimate of the CO2 flux from the (upper) mantle. The approach of using ratios (involving noble gas isotopes) has also been extended to island arcs. Marty et al. (1989) found significantly higher CO2/3He ratios in arc-related geothermal fluids than observed at mid-ocean ridges, consistent with addition of slab-derived CO2 to the mantle wedge. Sano and Williams (1996) scaled the CO2 flux to 3He, showing that the output of CO2 at subduction zones was comparable in magnitude to that at spreading ridges. Therefore, for CO2 at least, subduction zones also …